2019
DOI: 10.1029/2019gl083456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot He+ Ions on the Electron Pitch Angle Scattering Driven by H+, He+, and O+ Band EMIC Waves

Abstract: In this paper, we find that hot He + ions significantly alter the kinetic dispersion relation of electromagnetic ion cyclotron (EMIC) waves and thus strongly affect the wave-driven electron pitch angle scattering rates. Increasing hot He + ion parallel temperature, temperature anisotropy, or abundance raises the pitch angle scattering rates of MeV electrons driven by the H + band EMIC waves. During the electron resonance with the He + and O + band EMIC waves, the electron pitch angle scattering rates are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…H. Lee et al, 2012;Yuan et al, 2016). It is worth examining these three events in more details to check the presence of such hot helium ions and to determine whether this could have prevented electron precipitation by helium band waves below ∼2-3 MeV (Chen et al, 2013;Xiang et al, 2018;J. Yu et al, 2019).…”
Section: Discussion Of Several Particular Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…H. Lee et al, 2012;Yuan et al, 2016). It is worth examining these three events in more details to check the presence of such hot helium ions and to determine whether this could have prevented electron precipitation by helium band waves below ∼2-3 MeV (Chen et al, 2013;Xiang et al, 2018;J. Yu et al, 2019).…”
Section: Discussion Of Several Particular Eventsmentioning
confidence: 99%
“…H. Lee et al, 2012) which demonstrated that (i) very small populations of hot helium ions can lead to significant narrowing of the stop band between helium and hydrogen band waves and that (ii) this stop band remains detectable for He + ion density that is not very low and He + ion temperature that is not very high (e.g., see Figures 9-10 from J. H. Lee et al, 2012). Such small quantity of helium ions that are not very hot may be insufficient to prevent electron precipitation by helium band waves below ∼2-3 MeV (Chen et al, 2013;Xiang et al, 2018;J. Yu et al, 2019).…”
Section: Discussion Of Several Particular Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ambient electron density (n e ) is set to be 200 cm −3 according to the simulations of Chen et al (2009). Following previous studies (e.g., Ma et al, 2019;Meredith et al, 2003;Yu et al, 2019b), the ion concentration ratios are assumed to be η cp +η hp = 70%, η che = 20%, and η co = 10%. The parallel temperature (T ∥hp ) of hot proton is set to be 25 keV.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In fact, the cold plasma approximation is inappropriate when the hot plasmas are present, such as the hot particle injection from magnetotail during active times (e.g., Chen et al, 2011Chen et al, , 2019Silin et al, 2011). It has been found that the presence of hot particles can seriously modify the cold plasma dispersion relation and consequently strongly affect the quasi-linear diffusion coefficients (Chen et al, 2013(Chen et al, , 2019Ni et al, 2018;Yu et al, 2019b). However, the effects of hot plasmas on the nonlinear interactions of electrons with electromagnetic waves remain unknown.…”
Section: Introductionmentioning
confidence: 99%